PENGARUH KUALITAS PELAYANAN DAN BAGI HASIL TERHADAP KEPUTUSAN MENABUNG NASABAH BANK SYARIAH INDONESIA (BSI) KCP BATAM BATU AJI - anisa, tipani; Sunargo,S.E.,M.Sc (LPPM Universitas Putera Batam, 2022)
The purpose of this study is to ascertain how Bank Syariah Indonesia (BSI) KCP Batam Batu Aji's customers decide to save money. This study employs a quantitative methodology and includes 197 respondents in its sample. This study uses a questionnaire distribution as a method of data gathering. The validity test, reliability test, multiple regression test, F test, t test, and coefficient of determination are some of the analysis approaches employed in this study. The SPSS 26 application was used to process the data that met the criteria for the analytic procedures. The statistical test's findings show that the independent variables of service quality and profit sharing have an impact on the dependent variable of saving choices. The findings indicated that, according to the calculation of the coefficient of determination, the influence of the independent variables profit sharing and service quality on the dependent variable of saving decision is 0,532 or 53.2%, demonstrating that these variables can have an impact on that decision. While additional factors outside the scope of this study have an impact on the remaining 46.8%. This demonstrates that the decision to save money is significantly influenced by service quality and profit